On a safety criterion for column-like structure - Khiem, Nguyen Tien (Vietnam Journal of Mechanics, 2004)
The practical exploitation of engineering structures needs very much a simple criterion for checking safety of structures instead of reliability index that is very difficult to be computed within the probabilistic theory. This paper deals with establishment of a simple criterion for checking safety of column-like structure based on deterministic analysis. The criterion consists of bound of the flexural displacement at the top of column that is conducted from the displacement analysis combined with ultimate state for the structure.